Redundancja w mediach. Rozważania wstępne - Kula, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
Redundancy, most frequently discussed in works on computer science, telecommunications and the theory of information, denotes in linguistics the excess of information, i.e. this amount of information that exceeds the minimum required for a message to be understood. The excess, that can perform a number of essential functions in spoken and written text, has not yet been comprehensively addressed linguistically. A study on redundancy in modern media makes it possible to indicate – with the application of stylistic and pragmalinguistic tools – the methods for influencing the recipient. The present article considers such issues as the function of a redundant transmission of information (message) and its linguistic exponents. One of the most important tasks of redundancy, i.e. making a media statement more attractive, is presented in detail. The author also indicates a group of media messages in which redundancy is applied to blur or disintegrate the text and verbosity is conducive to its further convolutedness and esotericism.